Genocide and resistance Nr. 15(1) - Starkauskas, Juozas; Streikus, Arūnas; Venclauskas, Linas; Brandišauskas, Valentinas; Banionis, Juozas; Anušauskas, Arvydas; Čekutis, Ričardas; Zizas, Rimantas (Genocidas ir rezistencija, 2004)
Full Issue (paper copy scan)